The miR-29 family in hematological malignancies - Fišerová, Barbora; Bešše, Lenka; Sedlaříková, Lenka; Hájek, Roman; Ševčíková, Sabina (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND: MicroRNAs are short non-coding regulators of gene expression. The human miR-29 family consists of three members: miR-29a, miR-29b and miR-29c. Members of this family were found to be aberrantly expressed in various types of tumors, including hematological malignancies. This family was described to have both oncogenic and tumor suppressor features influencing various pathological processes, such as tumor growth and apoptosis. This review summarizes current knowledge about the miR-29 family in selected hematological malignancies. CONCLUSION: Recent research of miR-29 family in hematological malignancies has proven its oncogenic as well as tumor suppressive potential. Nevertheless, the level of current evidence is not sufficient, and data remain inconclusive.
Keywords: extracelulární matrix; Extracellular Matrix; nádorová transformace buněk; tumor supresorové geny; Cell Transformation, Neoplastic; proliferace buněk; apoptóza; Humans; lidé; MicroRNAs; stárnutí buněk; hematologické nádory; Hematologic Neoplasms; Cellular Senescence; mikro RNA; Apoptosis; Genes, Tumor Suppressor; Cell Proliferation